STUDYING HUMAN DEVELOPMENT TO KNOW THE RIGHT LEARNING METHODS: MEMPELAJARI PERKEMBANGAN MANUSIA UNTUK MENGETAHUI METODE PEMBELAJARAN YANG TEPAT - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Basically development refers to systematic changes in physical and psychological functions. Physical changes include basic biological development as a result of conception (fertilization of the ovum by sperm), and the result of the interaction of biological and genetic processes with the environment. Meanwhile, psychological changes involve the overall psychological characteristics of individuals, such as cognitive, emotional, social and moral development. Development can also be interpreted as "a process of change in an individual or organism, both physically (physically) and psychologically (spiritually) towards a level of maturity or maturity that takes place systematically, progressively, and continuously." Development is also adaptive, meaning that development occurs to deal with conditions in life (Papalia et al., 2009). For example, why then can the baby walk? Of course it is for supports the baby's mobility process because as they get older, a person's desire for exploration will increase and it will be impossible for him to continue to rely on other people to move from one place to another. Human development is one of the signs of the continuation of life, in which various events are contained which then shape the person to live and deal with the problems of his life. Real development doesn't happen in separate boxes but to simplify and facilitate the discussion, developments are often divided into several aspects. The learning method is a systematic way in a concrete form in the form of steps to streamline the implementation of a lesson. There are many learning methods with other names that can actually be covered by similar learning models. This is reasonable, because the learning model is a general conceptual framework that may still be related to certain learning methods. Especially in the world of education, developments need to be understood to determine appropriate and effective learning methods.